Fixed Point Theorem in Symmetric Space Employing (c)- comparison Functions and Binary relation (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we prove the results on existence and uniqueness of fixed points in the setting of symmetric space under ψ-contractions using a binary relation. We also provide some examples to illustrate our newly proved results.
Keywords: Symmetric space; binary relation; (c)-comparison functions